#mothersday: Constructions of motherhood and femininity in social media posts. (August 2022) - Capdevila, Rose; Dann, Charlotte; Lazard, Lisa; Roper, Sandra; Locke, Abigail
Images and representations of parenting, and particularly mothering, have become commonplace on social media platforms over the past decade. These displays, however, take place in the context of popular contemporary discourses around gender and parenting that are in many ways prescriptive. This paper explores the constructions of mothering online through an analysis of posts about mothers on Mother's Day from 2018 to 2020. Data were collected from Instagram and Twitter using hashtags such as #mothersday, #happymothersday and #motheringsunday. Both content and thematic analyses were conducted. This paper will consider three main themes that were identified in the data: "Beauty & biology"; "Grief & loss" and "Care (& COVID)", with a focus on constructions of gendered parenting and family through the explicit celebration of the lives and roles of mothers. The findings provide insight into normative constructions of gender and how these are mediated through the affordances of social media platforms in a neoliberal context.